The Determinants of Firm’s Value through Intellectual, Capital, Debt Policy, and Business Risk - Siti Nurhikmah; Raeesah Shalsabila Anjani Prameswary (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This study examines and analyzes the effect of debt policy, intellectual capital, and business risk on firm value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The independent variables used in this study are debt policy, intellectual capital, and business risk. Moreover, the dependent variable used in this study is firm value. The data used in this study is secondary data in the form of financial statements of each sample company reported to the IDX from 2015-2020. The sample in this study consisted of 12 food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2020 period. Sampling was done by using the purposive sampling method. The data analysis used in this Research is the panel data regression method with the help of Eviews version 10 software. The results of this study state that debt policy has a positive and significant effect on firm value in food and beverage companies. Intellectual capital positively and significantly affects firm value in food and beverage companies. At the same time, business risk has a positive but insignificant effect on company value in food and beverage companies.